Trends in online support seeking behavior among college students pre- and post COVID-19 pandemic - Bossing, Nathan (2024)
This research study will examine the changes in online help seeking behavior among college undergraduate students as a result of the COVID-19 pandemic. Focusing on how that help-seeking behavior changed between before and after the COVID-19 lockdowns, as well as other factors that have been identified by research which may relate to how effective the individual’s attempt to seek help was. To gather data, a survey will be developed via Qualtrics, and sent to undergraduate students enrolled in psychology courses at Western Carolina University. This survey will include a demographic section, a section which designed to assess the participants familiarity with technology, and a section which will examine trends in the participants online help-seeking behaviors before and after the lockdowns. This research should help provide further insight into changes that took place as a result of the pandemic, specifically in how individuals had to adapt their behaviors to obtain help from others that previously was done in-person.